2011
DOI: 10.2478/v10222-011-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, Antibacterial and Antifungal Activities of Tea Infusions from Berry Leaves, Carob and Doum

Abstract: This study is carried out to evaluate the chemical composition and physicochemical properties of berry leaves, carob and doum tea infusions and their mixtures. Furthermore, the antioxidant activities of these extracts were investigated by scavenging of 1,1 diphenyl-2-picrylehydrozyl (DPPH) radicals. The proliferation inhibition activities on some types of bacteria and yeast were also measured for evaluating the antimicrobial activity of berry leaves, carob and doum tea infusions and their blends. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Figures 1 and 2 showed that the combinations between aromatic plants were the most effective inhibitors followed by two mix and aromatic plants alone had a lesser effect. Synergistic effects were reported by Abdel-ElKalek [2008] and Hussein et al [2011b]. They reported that the combinations of spices extracts and herb tea infusions (berry leaves, dom and kharoub extracts) showed a greater inhibitory effect towards tested bacteria and fungi than that of individual extract.…”
Section: Effect Of Aromatic Plants On the Microbial Load Of The Piementioning
confidence: 77%
“…Figures 1 and 2 showed that the combinations between aromatic plants were the most effective inhibitors followed by two mix and aromatic plants alone had a lesser effect. Synergistic effects were reported by Abdel-ElKalek [2008] and Hussein et al [2011b]. They reported that the combinations of spices extracts and herb tea infusions (berry leaves, dom and kharoub extracts) showed a greater inhibitory effect towards tested bacteria and fungi than that of individual extract.…”
Section: Effect Of Aromatic Plants On the Microbial Load Of The Piementioning
confidence: 77%
“…Studies [30,34,35] continue to support the beneficial effects of TDF specifically in traditional fruit juice beverages in enhancing perceived satiety, regulating energy intake, modulating gastric emptying, and reducing weight gain. Previous studies [36][37][38][39][40][41][42] have also supported the potential activity of some traditional Egyptian beverages as functional foods with antioxidative, antihypertensive, hypolipidemic, and anti-carcinogenic properties particularly in hibiscus tea, tamarind juice, dried apricot juice, and carob juice. In addition, the potential benefits of guava, strawberries, and pomegranate for the prevention of obesity and obesity-related diseases have been previously demonstrated [43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 76%
“…Subsequently there is no need to the high level which increases the productive coast. (Hussein et al, 2011).…”
Section: Doe Traitsmentioning
confidence: 99%
“…Therefore there is a growing interest in the substances exhibiting antioxidant properties that are supplied to human and animal organisms as food components or a specific pharmaceutica. Hussein et al (2011) evaluated the chemical composition and physicochemical properties of doum tea infusions. Furthermore, the antioxidant activities of these extracts were investigated by scavenging of 1,1 diphenyl-2-picrylehydrozyl (DPPH) radicals.…”
Section: Introductionmentioning
confidence: 99%